Literature and Nation Building - Parappa Magadum, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Literature has long served as both a mirror of and a catalyst for social, political, and cultural change. In India, literature has been an essential tool for nation-building, giving a forum for the development of collective identity, cultural continuity, and political consciousness. This study investigates the complex relationship between literature and nation-building in India, focusing on how writers and philosophers have molded the national imagination from antiquity to the postcolonial era.
Keywords: Cultural Change; Catalyst; Identity; Political consciousness